Faktor-Faktor yang Mempengaruhi Pengambilan Kredit di LPD Desa Adat Pujungan, Kecamatan Pupuan, Kabupaten Tabanan - I KADEK ASTRAWAN; I KETUT SUAMBA; I DEWA GEDE RAKA SARJANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2020)
The Factors That Affect Credit Decision Making In LPD Of Pujungan Village, Pupuan Sub-District, Tabanan Regency One of the economic development in Indonesia is supported by the Rural Credit Institution(LPD) of Pujungan Village, Pupuan Sub-District, Tabanan Regency. The efforts tomaintain and increase its continuity, LPD also needs to look at the factors that affect thedebtor in making credit decisions. The purpose of this research is to determine the factorsthat influence the debtor’s decision in taking credit and the suitability of credit usage bythe debtor. The sampling technique in this research was carried out by random sampling.The analysis technique used is multiple linier regression analysis. The results showed thatinterest rates, services, and procedures for lending had a positive and significant effect ondebtor decisions in taking credit, and the suitability of use tends to productive loans.